Casual blood glucose and subsequent cardiovascular disease and all-cause mortality among 159 731 participants in Cohort of Norway (CONOR). Issue 1 (23rd February 2021) - Riise, Hilde Kristin Refvik; Igland, Jannicke; Sulo, Gerhard; Graue, Marit; Haltbakk, Johannes; Tell, Grethe Seppola; Iversen, Marjolein Memelink
Abstract : Introduction: Our aim was to assess the association between casual blood glucose level and subsequent cardiovascular disease (CVD) and mortality among community-dwelling adults without a diagnosis of diabetes. Research design and methods: In this community-based cohort study, 159 731 individuals with a measurement of casual blood glucose were followed from their participation date in Cohort of Norway (CONOR) (1994–2003) until a CVD episode, death or 31 December 2009. All analyses were done using Cox proportional hazard regression, and the results are reported as multivariable-adjusted HRs with 95% CI. Results: Compared with those with normal glucose levels (<7.8 mmol/L), participants categorized as having borderline (7.8–11.0 mmol/L) levels showed an increased risk of a stroke (HR 1.29; 95% CI 1.12 to 2.49) and cardiovascular (HR 1.29; 95% CI 1.12 to 2.48), and all-cause (HR 1.27; 95% CI 1.16 to 1.38) mortality, while participants with high glucose levels (>11.0 mmol/L) had an even more increased risk. One mmol/L increase in glucose level was associated with an increased risk of all four endpoints among participants with borderline as well as within normal glucose levels. In analyses stratified by sex and age group, the CVD risk estimates tended to be higher in women than in men and in those <65 years of age but no significant interactions were found. Conclusion: An increase in casual blood glucose levels, even within the range of normal and borderline levels, was positively associated with increased risk of CVD and mortality among community-dwelling adults without a known diagnosis of diabetes.